The medicinal properties of borage water in the story «El latín de una limeña» by Ricardo Palma - Cuadrado Beltrán, Abigail Noemí (2020)
This article will deal, from a medical point of view, with the most outstanding characteristics of the «agua de borrajas» plant, as described in the tradition «El latín de una limeña», a text that forms part of the famous Tradiciones peruanas, an exemplary work by Ricardo Palma. It is important to highlight, above all, the diuretic and sudorific properties that made the plant able to help with various ailments that afflicted the ancient society of Lima.